PENGARUH PENGGUNAAN KORSET LUMBAL TERHADAP PENURUNAN NYERI DYSMENORRHEA PRIMER PADA SISWI SMP NEGERI 2 MELAYA - Ni Made Dea Maretha; Ni Rai Sintya Agustini; Yohanes Zenriano Tarigan (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2025)
ABSTRACT Introduction : Primary Dysmenorrhea is a common complaint experienced by adolescent grils and can interfere with daily activities. One pf the non-pharmacolgical interventions that can help reduce dysmenorrhea pain is the use of a lumbar corset that functions to support posture and reduce muscle tension. Methods : This stdy used a pre-experimental design with a ne group pretest-posttest approach. The population in this study were studens of SMP Negeri 2 Melaya who experienced primary dysmenorrhea. A total of 47 respondents wwere selected using convenience sampling technique. The intervention eas carried out by wearing a lumbar corset for 2 hours per day during menstruation. Pain scale was measured beafor and after intervention using VAS pain scale sheet. Data were analyzed using Wilcoxon Signed Renk Test. Results : Before the intervention, most respondents experienced moderate to severe pain. After the use of the lumbar corset, there was a significant decrease in pain levels. The ilcoxon test shows a value of Z = 6,283 with P< 0.001, which means there is a significant difference between pain before and after the intervention. Discussion : The results showed that the use of lumbar corsets was effective in reducing primary dysmenorrhea pain in adolescent girls. Further research with a control group and a lerger sampel size isrecommended to strengthen the result.